The effect of transfer pricing, fixed asset intensity and inventory intensity on tax avoidance - Ramadhan, Muhammad Rizky; Arieftiara, Dianwicaksih (Educoretax, 2025)
This study aims to investigate the impact of transfer pricing, fixed asset intensity, and inventory intensity on tax avoidance. The population used in this study is manufacturing companies in the consumer goods sector listed on the IDX during the period 2020-2024. The sample selection technique used purposive sampling technique and obtained 15 companies for 5 years with a total sample data obtained of 74 sample data. Data processing using Microsoft Office Excel and STATA 12 program, by conducting panel data regression model analysis. The results of this study indicate that transfer pricing has no effect on tax avoidance, fixed asset intensity has no effect on tax avoidance, inventory intensity has a negative effect on tax avoidance, and simultaneously transfer pricing, fixed asset intensity and inventory intensity, have an effect on tax avoidance.